Improvement of in cylinder airflow using dissimilar valve lift in a compressed natural gas bi-fuel engine - D., Ramasamy (2015)
Bi-fuel conversions are a common alternative tuellmg option tor mono-tuel gasoline spark ignition (SI) vehicles because it requires only minor vehicle modifications. In Malaysia, most bi-fuel vehicles are fuelled with compressed natural gas (CNG) and gasoline. However, CNG flame speed is lower than gasoline resulting in, reduced power and range of the vehicle when operating on CNG. The lower flame speed also increases exhaust temperatures and can lead to premature exhaust valve degradation. Increasing the turbulence via swirl effect, can help improve the flame speed. A dissimilar valve lift profile was used to generate the swirl followed with engine testing concluding the performance, efficiency and emissions as the engine operates as a function of the air flow and fuel. Firstly, a flow bench was used to analyse swirl generated by dissimilar valve lift (DVL) profiles on the intake valve to find the conditions with the best swirl conditions. After that, a 3-dimensional engine simulation was used to predict the best DVL. In the simulation, both air intake and combustion of the engine was simulated. It was found that flame propagation was increased by 32.2%. During the intake the swirl number (2.25 SN) an increment of the turbulence kinetic energy (TKE) level was seen, which improves fuel mixing and flame speed. The best DVL setting was sent f9r fabrication. The design was tested on a 4-stroke engine and in-cylinder analysis was done. Further enhancement was achieved by advancing the ignition timing to 12 °CA from baseline. The turbulent flow and ignition timing advance gave a torque improvement of 6.1 % while BSFC was reduced by 13.4 % and efficiency improved by 11.8 % compared to the CNG baseline. The coefficient of variant in the indicated mean effective pressure (COVimep) also improved to 5.6 % at 4000 rpm signalling more stable combustion. Finally, emissions were reduced by 70 % for HC and 41 % for NOx. CO values was unchanged. The rate of heat release (ROHR) for the CNG ~ngine was more than gasoline when ignition was advanced.